Vos estis lux mundi: The Evolution of the Church's Response to Sexual Abuse and its Cover-up after the Vatican Summit - Renken, John A. (Studia canonica, 2019)
Following the so-called 'Vatican Summit' on 21-24 February 2019, Pope Francis issued his apostolic letter motu proprio Vos estis lux mundi whereby he expanded the offense and the offenders of sexual abuse of minors and vulnerable persons in the Church, identified certain rights of victims/survivors, and provided for a mechanism to investigate bishops and their equivalents who have committed this abuse or who have obstructed its investigation. This study is a commentary on this apostolic letter.